Practice and effective analysis of continuous quality improvement in nosocomial infection prevention and control (医院感染防控持续质量改进及效果) - XU Xu (徐旭); REN Guqun (任顾群); SU Yuqiang (苏玉强); XU Yuanle (许远乐); WANG Yuena (王岳娜) (中西医结合护理)
Objective To analyze the role and effect of continuous quality improvement in nosocomial infection prevention and control. Methods In order to improve the effect of nosocomial infection prevention and control, a set of continuous quality improvement measures had been carried out since January, 2021. Totally 500 hospitalized patients with hospital admission from January to December 2020 were selected as the control group, and 500 hospitalized patients with hospital admission from January to December 2021 were selected as the observation group, At the same time, 60 medical and nursing staffs were selected for clinical research. This study will evaluate the role and effect of continuous quality improvement in nosocomial infection prevention and control by comparing the differences in the occurrence of nosocomial infection between the two groups of patients, the scores of medical staff's mastery of nosocomial infection related knowledge at different time points, and the differences in the satisfaction of the two groups of patients with infection prevention and control. Results The incidence of incision infection, skin infection, urinary system infection and respiratory system infection in the observation group were significantly lower than those in the control group, and the difference between the groups was statistically significant (P < 0. 05). In 2020, the scores of hospital infection knowledge mastery among medical and nursing staffs in our hospital, such as safety protection, aseptic operation and occupational exposure, were significantly lower than those in 2021, with a significant difference (P < 0. 01). The satisfaction of patients in the observation group was higher than that in the control group, with a significant difference (P < 0. 01). Conclusion The implementation effect of continuous quality improvement measures in the prevention and control of nosocomial infection is remarkable. The implementation of this measure can not only improve the mastery of nosocomial infection related knowledge among hospital staffs, but also effectively reduce the risk of nosocomial infection. (目的 探讨持续质量改进在医院感染防控中的作用与实践效果。方法 医院为提升医院感染防控效果, 于2021年1月进行持续质量改进措施的施行。选取2020年1月—12月间在医院接受住院治疗的500例患者作为对照组, 另选取2021年1月—12月间在医院接受住院治疗的500例患者作为观察组; 同时抽取2020年1月—2021年12月间在医院工作的60名医护人员进行临床研究。对比两组患者的医院感染发生情况、不同时间点医护人员医院感染相关知识掌握程度评分和两组患者对于感染防控工作的满意度, 评析持续质量改进在医院感染防控中的作用与效果。结果 观察组患者的切口感染、皮肤感染、泌尿系统感染和呼吸系统感染发生率均低于对照组, 差异有统计学意义(P＜0. 05)。2020年度医院60名医护人员的安全防护、无菌操作和职业暴露等医院感染知识掌握评分均低于2021年度, 差异有统计学意义(P＜0. 01)。观察组患者对于感染防控工作的满意度高于对照组(P＜0. 01)。结论 持续质量改进措施在医院感染防控工作中的实施成效显著, 该措施的施行不仅能够提升医院工作人员的医院感染相关知识掌握程度, 还能效避免医院感染的发生。)